2023
DOI: 10.1111/nph.18734
|View full text |Cite
|
Sign up to set email alerts
|

DNA hypomethylation of the host tree impairs interaction with mutualistic ectomycorrhizal fungus

Abstract: Summary Ectomycorrhizas are an intrinsic component of tree nutrition and responses to environmental variations. How epigenetic mechanisms might regulate these mutualistic interactions is unknown. By manipulating the level of expression of the chromatin remodeler DECREASE IN DNA METHYLATION 1 (DDM1) and two demethylases DEMETER‐LIKE (DML) in Populus tremula × Populus alba lines, we examined how host DNA methylation modulates multiple parameters of the responses to root colonization with the mutualistic fungus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…Tantalising results from studies of pathogen-plant ckRNAi also open many avenues for future research; for instance, the loading of endosymbiont sRNAs into host AGO4 proteins opens the prospect of these driving transcriptional gene silencing, possibly allowing long-term regulation of gene expression in the host through methylation of target genes. Such regulation would have considerable benefits in a mutualism, potentially adapting one or both partners to increase the stability of the interaction; indeed, the importance of DNA methylation in symbiosis has been recently (Vigneaud et al, 2023). Determining whether this is observed in the AM symbiosis will be an important avenue for research, especially given that this could be modified to increase the stability of symbioses in key crops.…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tantalising results from studies of pathogen-plant ckRNAi also open many avenues for future research; for instance, the loading of endosymbiont sRNAs into host AGO4 proteins opens the prospect of these driving transcriptional gene silencing, possibly allowing long-term regulation of gene expression in the host through methylation of target genes. Such regulation would have considerable benefits in a mutualism, potentially adapting one or both partners to increase the stability of the interaction; indeed, the importance of DNA methylation in symbiosis has been recently (Vigneaud et al, 2023). Determining whether this is observed in the AM symbiosis will be an important avenue for research, especially given that this could be modified to increase the stability of symbioses in key crops.…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%
“…Such regulation would have considerable benefits in a mutualism, potentially adapting one or both partners to increase the stability of the interaction; indeed, the importance of DNA methylation in symbiosis has been recently demonstrated in ectomycorrhizal symbiosis, with hypomethylation in the Populus sp. host associated with decreased association with the Laccaria bicolor mycorrhizal fungus (Vigneaud et al ., 2023 ). Determining whether this is observed in the AM symbiosis will be an important avenue for research, especially given that this could be modified to increase the stability of symbioses in key crops.…”
Section: The Roles Of Srnas In Mutualistic Symbiosismentioning
confidence: 99%
“…Poplars are characterized by a high genetic diversity, fast juvenile growth, vegetative propagation capacity, and the genome of several species has been sequenced (Tuskan et al 2006;Mader et al 2016). Over the past decade, poplar has been widely used to investigate the role of DNA methylation in phenotypic plasticity and adaptation to environmental changes (Brautigam et al 2013;Lafon-Placette et al 2013Zhu et al 2013;Plomion et al 2016;Conde et al 2017;Le Gac et al 2018, 2019Sow et al 2018aSow et al , 2018bSow et al , 2021Vigneaud et al 2023). However, several open questions remain to be addressed, such as (i) does epigenetics play a role in genome reprogramming in response to polyploidization events?…”
Section: Introductionmentioning
confidence: 99%
“…In the case of arbuscular mycorrhizal (AM) symbiosis, studies have shown that epigenetic modifications occur in the seeds of Geranium sylvaticum, and the roots and leaves of Geranium robertianum, in symbiosis with the AM fungus Funneliformis mosseae (Varga & Soulsbury, 2017. In this issue of New Phytologist, Vigneaud et al (2023Vigneaud et al ( , pp. 2561Vigneaud et al ( -2577 analyzed gene regulation at the epigenetic level interfering with plant ectomycorrhizal (ECM) interactions.…”
mentioning
confidence: 99%
“…In this issue of New Phytologist , Vigneaud et al . (2023, pp. 2561–2577) analyzed gene regulation at the epigenetic level interfering with plant ectomycorrhizal (ECM) interactions.…”
mentioning
confidence: 99%